2016
DOI: 10.15406/jcpcr.2016.04.00109
|View full text |Cite
|
Sign up to set email alerts
|

Association of Menopausal Status with Pathological Features of Tumor in Stage I to III A Breast Cancer Patients Treated With Upfront Modified Radical Mastectomy

Abstract: Introduction: Breast cancer is the commonest malignancy diagnosed among women worldwide. In Pakistan around 90,000 women are diagnosed with breast cancer every year. Lymphnode involvement, tumor size, receptor status, tumor grade, presence of LVI, age and ethnicity are well recognized prognostic factors for breast cancer. The aim of this study was to evaluate the relationship of menopausal status with pathological and prognostic features of tumor in patients with stage I to III A breast cancer treated upfront … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(15 reference statements)
0
1
1
Order By: Relevance
“…Studies by Wilking N et al, [32] Faheem M et al, [33] and Mahmood H et al showed similar results. [34] In present study, we did not observe any significant correlation between axillary lymph node status with ER (p value=0.651), PR (p value=0.689) and HER2/neu (p value=0.594) expression in present study. Studies by Ambroise M et al, [19] Azizun Nisa et al, [35] showed similar results.…”
Section: Subtype4contrasting
confidence: 70%
“…Studies by Wilking N et al, [32] Faheem M et al, [33] and Mahmood H et al showed similar results. [34] In present study, we did not observe any significant correlation between axillary lymph node status with ER (p value=0.651), PR (p value=0.689) and HER2/neu (p value=0.594) expression in present study. Studies by Ambroise M et al, [19] Azizun Nisa et al, [35] showed similar results.…”
Section: Subtype4contrasting
confidence: 70%
“…Breast tumors in premenopausal women often have poor prognostic characteristics—higher stage and grade and estrogen receptor (ER) negative [ 16 , 17 ]. Accordingly, most premenopausal women are recommended taxane-based chemotherapy, followed by up to 10 years of tamoxifen therapy for those with ER+ tumors, whereas postmenopausal women to a greater extent can forego chemotherapy [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%